Radiofrequency Ablation for Treatment of Symptomatic Uterine Fibroids - Siân Jones; Peter O'Donovan; David Toub (Obstetrics and Gynecology International)
The use of thermal energy-based systems to treat uterine fibroids has resulted in a plethora of devices that are less invasive and potentially as effective in reducing symptoms as traditional options such as myomectomy. Most thermal ablation devices involve hyperthermia (heating of tissue), which entails the conversion of an external electromagnetic or ultrasound waves into intracellular mechanical energy, generating heat. What has emerged from two decades of peer-reviewed research is the concept that hyperthermic fibroid ablation, regardless of the thermal energy source, can create large areas of necrosis within fibroids resulting in reductions in fibroid volume, associated symptoms and the need for reintervention. When a greater percentage of a fibroid's volume is ablated, symptomatic relief is more pronounced, quality of life increases, and it is more likely that such improvements will be durable. We review radiofrequency ablation (RFA), one modality of hyperthermic fibroid ablation.